FIELD EVALUATION OF THE CYCLIC STRENGTH VERSUS CONE TIP RESISTANCE CORRELATION IN SILTY SANDS - Huang, An-Bin; Tai, Yuan-Yu; Lee, Wei F.; Huang, Yao-Tao (My University, 2009)
The liquefaction potential assessment under the framework of simplified procedure that involves the use of cone penetration tests (CPT) typically relies on empirical correlations between the soil cyclic resistance ratio, CRR and cone tip resistance q(t). For sands that contain fines (particles passing #200 sieve), an adjustment based on fines content in the CRR-q(t) correlation is called for in currently available procedures. Earlier laboratory calibration tests in reconstituted silty sand specimens performed by the authors have indicated that partial drainage in CPT played an important role in the CRR-q(t) correlations. A series of laboratory tests on undisturbed samples and field piezocone penetration tests (CPTU) were carried out in an alluvial soil deposit at two test sites in Central and Southern Taiwan. The results indicated that unlike the uniformly mixed specimens reconstituted in laboratory, the tested natural alluvial silt/sand soils can be heterogeneous with closely spaced clean sand layers embedded in a matrix of silty material. This stratification can render the CPTU a drained test even at fines contents well in excess of 50%. The ignorance of free draining effects on CPTU due to stratification in alluvial soils may lead to overestimation of CRR. Because of these factors, calibration of the CRR-q(t) correlations by performing tests in local soil and field procedures to ascertain the drainage conditions in CPTU are important to the proper application of the CRR-q(t) correlations in the liquefaction potential assessment.
Keywords: CPTU; fines content; liquefaction; sand; silt (IGC: D7/E7)